Dampak Libur Lebaran Terhadap Aktivitas Impor Tekstil di Indonesia - Khairani, Nayla Rumaisyha; Rahmadiani, Oktavia; Ardiyanti, Vida Rizqina; Flinch, David (Lembaga Publikasi Ilmiah Nusantara, 2024)
The Eid holiday is an important moment for Indonesia because it has an impact on various economic sectors, including the textile industry. During this period, the demand for textile products such as clothing and fabrics is increasing, both for daily needs and special occasions. One of the factors affecting the national textile product (TPT) textile market is the increase in textile imports when domestic demand is not met by local producers. The purpose of this study is to analyze the impact of textile imports on the local industry during the Eid holiday, both from the perspective of economy, labor, and local business sustainability. The data used in this study came from relevant literature sources. The results of the study show that although textile imports can meet high demand, it can weaken the competitiveness of local products and threaten the sustainability of the domestic textile industry. These impacts include reduced competitiveness of local products in the domestic market, threats to employment in the textile sector, and impacts on the sustainability of local producers, especially small and medium enterprises. Therefore, strategic steps are needed to help the domestic textile industry.